Corruption in America - ZEPHYR TEACHOUT (Harvard University Press, 2014)
When Benjamin Franklin left Paris in 1785 after several years representing American interests in France, Louis XVI gave him a gorgeous parting gift. It was a portrait of King Louis, surrounded by 408 diamonds â€œof a beautiful waterâ€ set in two wreathed rows around the picture, and held in a golden case of a kind sometimes called a snuff box. Th e snuff box and portrait were worth as much as fi ve times the value of other gifts given to diplomats. One historian has called it the â€œmost precious treasure in [Franklinâ€™s] entire estate.â€1 It depicted the king with powdered hair and red cheeks, wearing white lace around his throat, two gold chains on his shoulders, and a blue robe with gold fl eurs- de- lis.2 In Eu rope, gifts were socially required upon a diplomatâ€™s departure. A valuable gift indicated a regentâ€™s great favor and a job well done. But in the new United States, the snuff box signifi ed danger. Such a luxurious present was perceived as having the potential to corrupt men like Franklin, and therefore it needed to be carefully managed. In Eu rope, in other words, the gift had positive associations of connection and graciousness; in the United States, it had negative associations of inappropriate attachments and dependencies. Th e snuff box stood for friendship or old world corruption, respect or bribery, depending on the perspective. For the Americans it was a symbol of seduction, de penden cy, luxury, and a Eu ro pe an confusion about the proper relationship between politics, power and intimacy, and friendship.